Intergenerational Transmission of Educational Attitudes in Chinese American Families: Interplay of Socioeconomic Status and Acculturation - Shen, Yishan (Child Dev, 2016)
This longitudinal study examined the influence of parents’ educational attitudes on adolescents’ educational attitudes and identified antecedents (i.e., parent education, family income, and parent acculturation), consequences (i.e., academic achievement and engagement), and a potential moderator (i.e., adolescent acculturation) of the transmission process. The sample was 444 Chinese American mothers, fathers, and adolescents (12–15 at W1). Using path analysis, this study found significant two-way interactions among parent education, income, and acculturation in predicting parents’ concurrent positive educational attitudes, which, in turn, predicted adolescents’ attitudes at W2. The latter link was further moderated by W1 and W2 adolescent acculturation for mother-adolescent and father-adolescent dyads. Adolescents’ positive educational attitudes at W2, in turn, were positively associated with their concurrent academic achievement and engagement.